Progress of endocytic CHRN to autophagic degradation is regulated by RAB5-GTPase and T145 phosphorylation of SH3GLB1 at mouse neuromuscular junctions in vivo - Wild, Franziska (Autophagy, 2016)
Endocytosed nicotinic acetylcholine receptors (CHRN) are degraded via macroautophagy/autophagy during atrophic conditions and are accompanied by the autophagic regulator protein SH3GLB1. The present study addressed the functional role of SH3GLB1 on CHRN trafficking and its implementation. We found an augmented ratio of total SH3GLB1 to threonine-145 phosphorylated SH3GLB1 (SH3GLB1:p-SH3GLB1) under conditions of increased CHRN vesicle numbers. Overexpression of T145 phosphomimetic (T145E) and phosphodeficient (T145A) mutants of SH3GLB1, was found to either slow down or augment the processing of endocytic CHRN vesicles, respectively. Co-expression of the early endosomal orchestrator RAB5 largely rescued the slow processing of endocytic CHRN vesicles induced by T145E. SH3GLB1 phosphomutants did not modulate the expression or colocalization of RAB5 with CHRN vesicles, but instead altered the expression of RAB5 activity regulators. In summary, these findings suggest that SH3GLB1 controls CHRN endocytic trafficking in a phosphorylation- and RAB5-dependent manner at steps upstream of autophagosome formation.